Sophora flavescens Alkaloids and Corticosteroid Synergistically Augment IL-10/IL-5 Ratio with Foxp3-Gene-Epigenetic Modification in Asthma PBMCs - Song, Ying; Wang, Zhen-Zhen; Wang, Lixin; Faybusovich, Paul; Srivastava, Kamal; Liu, Changda; Tversky, Jody; Dunkin, David; Busse, Paula; Ren, Xianqing; Miller, Rachel; Miao, Mingsan; et al. (Journal of asthma and allergy, 2021)
It has been demonstrated that ASHMI (antiasthma-simplified herbal medicine intervention) can improve airway function and reduce inflammation in human asthmatic patients with high safety and tolerability. In addition, ASHMI significantly suppresses Th2 cytokine production and increases Th1 cytokine production in treating asthma. Allergic asthma is associated with dysregulation of cytokines. We focused on IL-5 and IL-10 as signature Th2 and Treg cytokines to characterize ASHMI immunomodulatory components. The effects of ASHMI and individual herbal constituents on IL-5 and IL-10 production by PBMCs from asthmatic subjects were determined ex vivo. (SF)-F2, containing alkaloid compounds, effects on PBMC IL-10 and IL-5 production in the presence or absence of dexamethasone (Dex), and on DNA methylation levels at the gene promoter were determined. The ratio of anti-CD3/CD28 stimulated IL-10/IL-5 production by PBMCs from asthmatic subjects was significantly reduced compared to healthy subjects. In PBMCs from asthmatic subjects, ASHMI significantly reduced IL-5 production and increased IL-10 secretion in a dose-dependent manner (p < 0.05-0.01). SF-F2 was most effective in increasing IL-10, whereas SF-F4 (flavonoid compounds) was most effective in suppressing IL-5 production. Dex-treated PBMCs from asthma subjects showed a trend of increasing ratio of IL-10/IL-5 while demonstrating reduced levels in both IL-5 and IL-10 (p < 0.05). Co-culture with Dex and SF-F2 significantly prevented Dex suppression of IL-10, while retained Dex-suppression of IL-5 production, and increased IL-10/IL-5 ratio by Dex. Co-culture with SF-F2 and Dex significantly reduced DNA methylation levels at the gene promoter at CpG . The SF alkaloid-rich fraction may be responsible for ASHMI induction of IL-10 production by PBMCs and plays a synergistic effect with Dex for augmenting IL-10/IL-5 ratio.